Objective measurement of levels and patterns of physical activity. Issue 11 (13th September 2007) - Riddoch, Chris J; Mattocks, Calum; Deere, Kevin; Saunders, Jo; Kirkby, Jo; Tilling, Kate; Leary, Sam D; Blair, Steven N; Ness, Andy R
Abstract : Objective: To measure the levels and patterns of physical activity, using accelerometers, of 11-year-old children participating in the Avon Longitudinal Study of Parents and Children (ALSPAC). Design: Cross-sectional analysis. Setting: ALSPAC is a birth cohort study located in the former county of Avon, in the southwest of England. This study used data collected when the children were 11 years old. Participants: 5595 children (2662 boys, 2933 girls). The children are the offspring of women recruited to a birth cohort study during 1991–2. The median age (95% CI) of the children is now 11.8 (11.6 to 11.9) years. Methods: Physical activity was measured over a maximum of 7 consecutive days using the MTI Actigraph accelerometer. Main outcome measures: Level and pattern of physical activity. Results: The median physical activity level was 580 counts/min. Boys were more active than girls (median (IQR) 644 (528–772) counts/min vs 529 (444–638) counts/min, respectively). Only 2.5% (95% CI 2.1% to 2.9%) of children (boys 5.1% (95% CI 4.3% to 6.0%), girls 0.4% (95% CI 0.2% to 0.7%) met current internationally recognised recommendations for physical activity. Children were most active in summer and least active in winter (difference = 108 counts/min). Both the mother and partner's education level were inversely associated with activity level (p for trend <0.001 (both mother and partner)). The association was lost for mother's education (p for trend = 0.07) and attenuated for partner's education (p for trend = 0.02), after adjustment for age, sex, season, maternal age and social class. Conclusions: A large majority of children are insufficiently active, according to current recommended levels for health.